The Effect of Social Assistance Programs on Human Development Index in Central Java - Anawati, Triski; Retno Febriyastuti Widyawati (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
This analysis focuses of this research is identifying the effect of social assistance programs on the Human Development Index (HDI) in Central Java Province during the period 2019-2023. The analyzed programs include Non-cash Food Assistance (BPNT), Smart Indonesia Program (PIP), Contribution Assistance Recipients (PBI), and Family Hope Program (PKH). The research employs a panel data regression analysis using the Fixed Effect Model, processed with EViews 12 software. The findings reveal that BPNT, PKH, and PBI have a positive and statistically significant effect on the Human Development Index, while PIP shows a negative and statistically insignificant effect on the Human Development Index in Central Java Province on 2019-2023. Keywords: HDI; Social Assistance; BPNT; PKH; PBI